2003
DOI: 10.1016/s0375-9474(02)01392-1
|View full text |Cite
|
Sign up to set email alerts
|

On the asymmetry of Gamow–Teller β-decay rates in mirror nuclei in relation with second-class currents

Abstract: The theoretical evaluation of major nuclear structure effects on the asymmetry of allowed GamowTeller β-decay rates in light mirror nuclei is presented. The calculations are performed within the shell model, using empirical isospin-nonconserving interaction and realistic Woods-Saxon radial wave functions. The revised treatment of p-shell nuclei is supplemented by systematic calculations for sdshell nuclei and compared to experimental asymmetries when available. The results are important in connection with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 68 publications
(150 reference statements)
1
31
0
1
Order By: Relevance
“…Although this contribution is expected to be small considering the small isotopic ratio of 0.33% for 43 Ca, we could not estimate it properly. We also found that 2.223 MeV, 3.224 MeV, and 3.393 MeV peaks are contaminated by the 44 Sc GT excitations by comparing the present 42 Sc spectrum with that of the 44 Ca( 3 He, t) 44 Sc reaction given in Ref. [32].…”
Section: Excitations From Contaminant Isotopesmentioning
confidence: 57%
See 4 more Smart Citations
“…Although this contribution is expected to be small considering the small isotopic ratio of 0.33% for 43 Ca, we could not estimate it properly. We also found that 2.223 MeV, 3.224 MeV, and 3.393 MeV peaks are contaminated by the 44 Sc GT excitations by comparing the present 42 Sc spectrum with that of the 44 Ca( 3 He, t) 44 Sc reaction given in Ref. [32].…”
Section: Excitations From Contaminant Isotopesmentioning
confidence: 57%
“…Therefore, our result suggests that the total sum of the B(GT) strength located in fragmented discrete states in the E x region up to 12 MeV is less than half of the sum-rule-limit value. A small summed GT strength of ≈ 40% compared to the Ikeda sum rule is also reported in the 44 Ca( 3 He, t) 44 Sc measurement analyzed up to E x ≈ 14 MeV [32]. Similarly, in a recent analysis of the 48 Ca(p, n) 48 Sc measurement performed up to a higher E x of ≈ 30 MeV, a relatively small total GT strength of ≈ 65% of the sum-rule-limit value was suggested even if the ∆L = 0 strength in the continuum caused by the QFS is included [58].…”
Section: A Gamow-teller Strength Distributionmentioning
confidence: 58%
See 3 more Smart Citations